Maternal perception of decreased fetal movements from maternal and fetal perspectives, a cohort study - Sheikh, Mahdi (BioMed Central, 2014)
BACKGROUND: Maternal counting of fetal movement is a popular and valuable screening tool of fetal wellbeing, however it is still not known what percentage of healthy pregnant women who gave birth to healthy term newborns had experienced decreased fetal movements during gestation and what maternal and fetal factors are associated with this maternal perception of decreased fetal movements. The aim of this study was to assess the associations between maternal perception of decreased fetal movements and maternal and fetal factors in normotensive singleton pregnancies with good pregnancy outcome. METHODS: This study was conducted on 729 normotensive singleton pregnant women who had referred for prenatal visit and on follow up gave birth to healthy term newborns. A questionnaire was completed for the participants and ultrasound imaging was performed. Participants were asked to count their fetal movements for one hour/3times/day. Participants were followed till delivery to exclude mothers with preterm and/or small for gestational age delivery from the study. RESULTS: Perception of decreased fetal movement was independently associated with maternal employment (Odds Ratio (OR), 2.66; 95% Confidence Interval (95% CI), 1.35–5.23), not having daily exercise (OR, 4.38; 95% CI, 1.56-8.08) and maternal supine position (OR, 3.85; 95% CI, 1.71–8.83). CONCLUSIONS: 8.1% of healthy pregnant women who have good pregnancy outcome report perception of decreased fetal movement when asked to count their fetal movement in third gestational trimester which is independently associated with maternal employment, supine position on counting and not having daily exercise.